2020
DOI: 10.1038/s41419-020-03072-x
|View full text |Cite|
|
Sign up to set email alerts
|

NLRP3-dependent microglial training impaired the clearance of amyloid-beta and aggravated the cognitive decline in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD), the most common form of dementia, is marked by progressive cognitive decline, deposition of misfolded amyloid-β (Aβ) peptide and formation of neurofibrillary tangles. Recently, microglial training has emerged as an important contributor to neurological diseases, which augments the subsequent inflammation. However, how it affects the pathology of AD remains unknown. Here, using a mouse model of sporadic Alzheimer’s disease (SAD) induced by streptozotocin injection, we demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
1
33
0
1
Order By: Relevance
“…The COVID-19 patients have a higher level of NLRP3 inflammasome activation that in combination with interleukin-18 and interleukin-1β have been shown to adversely impact cerebral function [ 22 ]. Also, NLRP3 inflammasome-mediated systemic inflammation can lead to pathological accumulation of the peptides/proteins such as fibrillar amyloid-β resulting in the induction and aggravation of neurodegenerative illnesses such as Alzheimer's disease [ 146 , 147 ]. It has been suggested that SARS-COV-2 infection may impair cognitive function that would lead to brain fog via selective targeting of the mitochondria of the neurons [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 patients have a higher level of NLRP3 inflammasome activation that in combination with interleukin-18 and interleukin-1β have been shown to adversely impact cerebral function [ 22 ]. Also, NLRP3 inflammasome-mediated systemic inflammation can lead to pathological accumulation of the peptides/proteins such as fibrillar amyloid-β resulting in the induction and aggravation of neurodegenerative illnesses such as Alzheimer's disease [ 146 , 147 ]. It has been suggested that SARS-COV-2 infection may impair cognitive function that would lead to brain fog via selective targeting of the mitochondria of the neurons [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 patients have a higher level of NLRP3 inflammasome activation that in combination with interleukin-18 and interleukin-1β have been shown to adversely impact cerebral function (22). Also, NLRP3 inflammasome mediated systemic inflammation can lead to pathological accumulation of the peptides/proteins such as fibrillar amyloid-β resulting in the induction and aggravation of neurodegenerative illnesses such as Alzheimer's disease (150,151). It has been suggested that SARS-COV-2 infection may impair cognitive function that would lead to brain fog via selective targeting of the mitochondria of the neurons (96).…”
Section: ) Pathophysiologymentioning
confidence: 99%
“…In a mouse model of sporadic Alzheimer’s disease (SAD) induced by streptozotocin (STZ) injection, the levels of NLRP3 in the cortex and hippocampus were increased in the STZ group compared with those in the sham group (He et al 2020 ). The symptoms of SAD, such as neuronal dysfunction, neuronal loss, and amyloid-β deposition, were aggravated by LPS treatment in an NLRP3-dependent manner, and genetic deletion of NLRP3 or an NLRP3 inhibitor, MCC950, prevented SAD symptoms via inhibition of NLRP3 inflammasome activation (He et al 2020 ).…”
Section: Nlrp3 Inflammasome-associated Diseasesmentioning
confidence: 99%